PEMANFAATAN KOMPOS DAUN LAMTORO (LEUCAENA LEUCOCEPHALA) DAN DAUN ANGSANA (PTEROCARPUS INDICUS) SEBAGAI MEDIA KULTUR PERTUMBUHAN POPULASI CHAETOCEROS CALCITRANS - SAFITRI, ANI (LenteraBio: Berkala Ilmiah Biologi, 2013)
This study aimed to determine the effect of compost made ??from lamtoro leaves and Angsana leaves in culture medium on the growth of population C. calcitrans at variety of doses and determine the right doses compost for optimal growth of C. calcitrans. The method used in this study was experimental with completely randomized design (CRD). Research using one factor was the administration of compost treatment consisted of A (control) in the form of urea 10 mg + 5 mg TSP; B (63 mg), C (94 mg), and D (126 mg). Each treatment carried out four times, so the total sample of 16. Observational study was conducted over 8 days. Parameters measured were growth in the number of cell C. calcitrans. Data were analyzed descriptively. Based on the results obtained, it could be concluded that the mix of compost made ??from lamtoro leaves and angsana leves into the culture medium revealed the differences in the growth of C. calcitrans and the optimal doses compost that affect the population growth of C. calcitrans was treatment D (2 times the doses of compost which was 126 mg / ml).   Key words: Compost of lamtoro leaves and angsana leaves; culture medium; growth of population; Chaetoceros calcitrans